Uso di gvSIG e SEXTANTE per la perimetrazione degli ambiti periurbani - Nolè, Gabriele; Murgante, Beniamino; Falciano, Antonio (GEOmedia, 2010)
Use of gvSIG and SEXTANTE for the perimetration of periurban areas The periurban fringe is the portion of land with characteristics of urbanization that cannot be considered neither urban nor rural. These areas are often characterized by a building expectancy, whose detection requires careful consideration of several territorial and environmental variables. It was implemented using a model of spatial analysis based on kernel Density Estimation (KDE) for the detection of periurban areas. The model is tested in the province of Potenza using gvSIG and SEXTANTE on Ubuntu Linux.